Efecto del consumo de Polymnia Sonchifolia (Yacón) en los niveles de lípidos en pacientes dislipidémicos del Centro Geriátrico del Hospital Naval, julio-noviembre del 2005 - Collantes Cossío, María (2019)
Objective: The objective was to determine the effect of Smallanthus Sonchifolius on serum cholesterol and plasmatriglycerides in dyslipidemic patients. Methodology: This is a prospective, pre-experimental and analytical study.The non random sample consisted of 50 patients. The control group consisted of 18 patients while the treatmentgroup consisted of 32 patients. Results: The yacon consumption significantly reduced (p <0.05) mean levels ofVLDL (from 38.1 to 30.2 mg / dl), LDL (from 184.1 to 153.6 mg / dl), total cholesterol (from 267 to 230.1 mg / dl)and triglycerides (149.4 to 185.2 mg / dl) without changing HDL cholesterol levels were maintained similar to theend of the study. Overall, the impact on these variables decreased significantly (p <0.05) cardiac risk (6.0 to 5.0).Conclusions: Daily consumption of yacon has been shown to reduce significantly (p <0.05) mean levels of VLDL,LDL, total cholesterol and triglycerides without affecting HDL cholesterol levels